Tim4‐Functionalized HBEV‐Chip by Isolating Plasma‐Derived Phosphatidylserine‐Positive Small Extracellular Vesicles for Pan‐Cancer Screening (Adv. Mater. Technol. 7/2022). Issue 7 (12th July 2022) - Yang, Liu; Tong, Xuedong; Zhang, Yong; Li, Yan; Liu, Jiangwei; Yin, Ruiling; Zeng, Dong; Yuan, Yue; Deng, Kun
Abstract : Pan‐Cancer Screening In the background of the inside cover, highlighting article number 2101115 by Kun Deng and co‐workers, the body is primarily made up of lung, colorectum, pancreas and blood vessels, which represents the concept of pan‐cancer screening in tumor liquid biopsy. The drop of blood entrances into HB EV‐Chip are indicating the isolation of tumor‐derived small extracellular vesicles from microlitre volume plasma for pan‐cancer screening in clinic and the high quality materials for mass spectrometry detection in lab.